Preliminary Investigations About the Cs*+H2 Collision. Issue 5 (1983) - Gadea, X. F.; Jeung, G. H.; Pelissier, M.; Malrieu, J. P.; Picque, J. L.; Rahmat, G.; Verges, J.; Vetter, R.
Abstract : The possible photoreactions leading to the formation of "laser snow" in cell experiment by laser irradiation of Cesium atoms to the (7 p ) level will be analyzed through crossed beam experiment. A single collision process would be excluded if an activation barrier was present in the inverse ground state reactionCsH + H → Cs + H 2 ; accurate ab initio calculations exclude the existence of such a barrier. The ionic state Cs + +H 2 − is suggested to make possible the electronic into vibrational energy transfer in the perpendicular collision.